2021
DOI: 10.3389/fbioe.2021.730938
|View full text |Cite
|
Sign up to set email alerts
|

Mobilizing Endogenous Repair Through Understanding Immune Reaction With Biomaterials

Abstract: With few exceptions, humans are incapable of fully recovering from severe physical trauma. Due to these limitations, the field of regenerative medicine seeks to find clinically viable ways to repair permanently damaged tissue. There are two main approaches to regenerative medicine: promoting endogenous repair of the wound, or transplanting a material to replace the injured tissue. In recent years, these two methods have fused with the development of biomaterials that act as a scaffold and mobilize the body’s n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 166 publications
(255 reference statements)
1
6
1
Order By: Relevance
“…After the acute inflammatory phase subsides, the macrophage population shifts to an M2 phenotype. M2 macrophages are characterized by the secretion of anti-inflammatory mediators (IL-10) and growth factors (PDGF and TGF-β) that aid in tissue healing by stabilizing angiogenesis (Karkanitsa et al, 2021;Martin and García, 2021). In our study, we observed the coexpression of M1 and M2 markers (Figure 6), which has usually been reported in FBR induced by scaffolds (Witherel et al, 2019).…”
Section: Discussionsupporting
confidence: 75%
“…After the acute inflammatory phase subsides, the macrophage population shifts to an M2 phenotype. M2 macrophages are characterized by the secretion of anti-inflammatory mediators (IL-10) and growth factors (PDGF and TGF-β) that aid in tissue healing by stabilizing angiogenesis (Karkanitsa et al, 2021;Martin and García, 2021). In our study, we observed the coexpression of M1 and M2 markers (Figure 6), which has usually been reported in FBR induced by scaffolds (Witherel et al, 2019).…”
Section: Discussionsupporting
confidence: 75%
“…Not only proteins of the immune system associated with a material but also platelets activated on its surface stimulate the activation of neutrophils [ 1 , 48 ]. Platelets are best known as key players in thrombosis and hemostasis; recent data demonstrate the important immune and inflammatory roles of platelets in both health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, fibroblasts will be recruited and activated and will produce collagen, causing the formation of a fibrous capsule around the implant. This collagenous fibrous capsule will not only isolate the implanted material from the surrounding tissues but will also impair its function [ 13 , 14 , 15 , 16 , 17 ].…”
Section: The Neutrophil In the Foreign Body Response To Biomaterialsmentioning
confidence: 99%